2022
DOI: 10.1111/joa.13777
|View full text |Cite
|
Sign up to set email alerts
|

A morphological study of the shape of the corpus callosum in normal, schizophrenic and bipolar patients

Abstract: Abnormalities in the morphology of the corpus callosum have been found to be involved in cognitive impairments or abnormal behaviour in patients with mental disorders such as schizophrenia and bipolar disorder. The present study investigated morphological shape differences of the corpus callosum in a large cohort of 223 participants between normal, schizophrenic and bipolar patients on MRI scans, CT scans and cadaver samples. Healthy samples were compared to a mental disorder population sample to determine mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Most CC fibers connect corresponding left and right cortical regions of the brain, with the organization, development of axonal elongation, and myelination of callosal fibers being correlated with the rostro-caudal (front-to-back) distribution of functional areas 5,6 . Regional alterations in CC shape are easily assessed with neuroimaging studies, which have found local callosal abnormalities in complex neurodevelopmental and neuropsychiatric disorders [6][7][8][9][10][11] , such as lower anterior volumes in autism 12 and lower posterior thickness in bipolar disorder 13 . Twin studies show up to 66% heritability for CC area 14,15 , and previous single-cohort studies of genetic influences on CC volume and its relationship to neuropsychiatric disorders have found heritability estimates between 22-39% 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…Most CC fibers connect corresponding left and right cortical regions of the brain, with the organization, development of axonal elongation, and myelination of callosal fibers being correlated with the rostro-caudal (front-to-back) distribution of functional areas 5,6 . Regional alterations in CC shape are easily assessed with neuroimaging studies, which have found local callosal abnormalities in complex neurodevelopmental and neuropsychiatric disorders [6][7][8][9][10][11] , such as lower anterior volumes in autism 12 and lower posterior thickness in bipolar disorder 13 . Twin studies show up to 66% heritability for CC area 14,15 , and previous single-cohort studies of genetic influences on CC volume and its relationship to neuropsychiatric disorders have found heritability estimates between 22-39% 16,17 .…”
Section: Introductionmentioning
confidence: 99%